Impact of a comprehensive prevention programme aimed at reducing incivility and verbal violence against healthcare workers in a French ophthalmic emergency department: an interrupted time-series study. Issue 9 (5th September 2019) - Touzet, Sandrine; Occelli, Pauline; Denis, Angelique; Cornut, Pierre-Loïc; Fassier, Jean-Baptiste; Le Pogam, Marie-Annick; Duclos, Antoine; Burillon, Carole
Abstract : Objective and setting: Primary prevention, comprising patient-oriented and environmental interventions, is considered to be one of the best ways to reduce violence in the emergency department (ED). We assessed the impact of a comprehensive prevention programme aimed at preventing incivility and verbal violence against healthcare professionals working in the ophthalmology ED (OED) of a university hospital. Intervention: The programme was designed to address long waiting times and lack of information. It combined a computerised triage algorithm linked to a waiting room patient call system, signage to assist patients to navigate in the OED, educational messages broadcast in the waiting room, presence of a mediator and video surveillance. Participants: All patients admitted to the OED and those accompanying them. Design: Single-centre prospective interrupted time-series study conducted over 18 months. Primary outcome: Violent acts self-reported by healthcare workers committed by patients or those accompanying them against healthcare workers. Secondary outcomes: Waiting time and length of stay. Results: There were a total of 22 107 admissions, including 272 (1.4%) with at least one act of violence reported by the healthcare workers. Almost all acts of violence were incivility or verbal harassment. The rate of violence significantly decreased from the pre-intervention to the intervention period (24.8, 95% CI 20.0 to 29.5, to 9.5, 95% CI 8.0 to 10.9, acts per 1000 admissions, p<0.001). An immediate 53% decrease in the violence rate (incidence rate ratio=0.47, 95% CI 0.27 to 0.82, p=0.0121) was observed in the first month of the intervention period, after implementation of the triage algorithm. Conclusion: A comprehensive prevention programme targeting patients and environment can reduce self-reported incivility and verbal violence against healthcare workers in an OED. Trial registration number: NCT02015884